Part A: Outlining the current state of AAVs & evaluating albumins potential role in AAV stability / Part B: Comparing separation resolution of multiple SEC columns & evaluating AAV-albumin interactions - Hughes, Oliver (2024)
Part A: Adeno-associated viral vectors are pivotal to the advancement of gene therapy, offering a promising vehicle for delivering genetic material with high efficiency and low pathogenicity. This literature review provides an analysis of the role of AAVs in gene therapy, highlighting recent developments and therapeutic outcomes across various genetic disorders. Current obstacles in AAV-based therapies such as physical stability and vector size limitations are also discussed. A significant focus is placed on the strategy of coupling AAVs with albumin to enhance vector performance and extend the expression duration of therapeutic genes. The review also outlines implications of this conjugation on the data derived from analytical techniques. It examines how this modification influences the accuracy and reliability of methods such as ELISA, qPCR, SEC-MALS and more. Findings from multiple studies provides insight into how albumin integration into AAV vectors might revolutionise gene delivery methods, potentially overcoming some of the current limitations in gene therapy research and application.